Can Kangoo Jump Shoes effect plantar-dorsiflexion strength and dynamic balance ability of badminton players? - Kesilmis, I.; Akin, M. (International Journal of Applied Exercise Physiology, 2019)
The aim of this study was to understand the effect of training with kangoo jump shoes (KJS) on the development of dynamic balance and plantar-dorsiflexion strength and also to investigate the correlation between dynamic balance and plantar-dorsiflexion strength of badminton players. Totally 60 females participated voluntarily with the mean age of 12.78±.88 year and were divided into three groups, named kangoo-badminton (KBG), badminton (BG) and control (CG). The dynamic balance was measured with the prokin tecno body for bipedal-right-left foot. The Lafayette Manual Muscle Testing System was used for strength measurements. For statistical analysis, the Kruskal Wallis H test and Wilcoxon Signed Rank tests were used. After post-test measurements there were statistically significant differences in bipedal dynamic balance ability, right-left plantar flexion peak, left dorsiflexion peak (p<.05) in favor of the KBG. And according to pre-test and post-test analyses of all three groups, there were statistically significant differences in bipedal-right-left foot dynamic balance ability, right-left plantar flexion peak, right dorsal flexion peak and left dorsal flexion peak in the KBG. In the BG, according to pre-test post-test comparison, there were statistically significant differences in the right-left dynamic balance ability and right-left plantar-dorsal flexion peak (p<.05). There was a positive correlation between the left foot plantar flexion peak and the left foot dynamic balance (r=.337**). There was a negative correlation between the left foot dorsiflexion peak and the bipedal dynamic balance (r=-.333**). There was no statistically significant difference in the CG (p>.05). It is obvious that, the fun workouts with the KJS enhance the balance and plantar-dorsiflexion strength development of the participants and make the trainings more enjoyable.